Critical Elements for a Multi‐Constellation Advanced RAIM. Issue 1 (20th March 2013) - Blanch, Juan; Walter, Todd; Enge, Per; Wallner, Stefan; Amarillo Fernandez, Francisco; Dellago, Riccardo; Ioannides, Rigas; Fernandez Hernandez, Ignacio; Belabbas, Boubeker; Spletter, Alexandru; Rippl, Markus
ABSTRACT: The GNSS environment is experiencing two major changes: the introduction of a new civil signal in the L5 band and the launch of new GNSS constellations. These improvements could enable worldwide vertical guidance using Advanced Receiver Autonomous Integrity Monitoring (ARAIM). Before ARAIM can be implemented, it will be necessary to develop a common understanding across service providers of the navigation requirements, the threat model, the airborne algorithm, and the role of ground monitoring. We outline a concept for the provision of integrity based on ARAIM. First, an interpretation of vertical guidance (LPV‐200) requirements is proposed. Then, we describe a comprehensive threat model for GNSS which includes both nominal performance and faulted behavior. We will show how the threats could be mitigated through the use of ground monitoring and the Integrity Support Message in addition to the ARAIM airborne algorithm. Finally, examples of constellation configurations providing worldwide coverage of LPV‐200 are presented. Copyright © 2013 Institute of Navigation.